Electric Vehicle Charging Network Planning for Maximizing Charging Service Capability and Operational Efficiency - ZHANG Xinsong; XU Yangyang; YUAN Yue; ZHU Junpeng (Nantong Daxue xuebao. Ziran kexue ban)
To maximize the charging service capability and operational efficiency simultaneously, a method is proposed to optimize the locations of electric vehicle charging station(EVCS) and the numbers of charging piles installed in each EVCS. For EVCS network, the charging service capability can be quantified by the traffic flow captured by the EVCS network, and the operational efficiency can be measured by the matching extent between the traffic flow captured by each EVCS and the number of charging piles equipped in each EVCS. The EVCS network planning is formulated as a multi-objective optimization problem, which is decoupled into two single-objective optimization problems that are solved in turn. Firstly, the locations of each EVCS are optimized by genetic algorithm to enhance service capability of the EV charging network. Secondly, the charging piles equipped in each EVCS are optimized by solving a nonlinear integer programming to improve operational efficiency of the EV charging network. At last, the simulation results of a 25-node traffics system demonstrate that: 1) the presented model and method is effective, which can provide a reasonable EVCS network planning; 2) maximum endurance mileage of the EV has significant impacts on the EVCS network planning, which should be the crucial factor in the EVCS network planning.